Single-swap editing for the correction of common Duchenne muscular dystrophy mutations - Andreas C. Chai; Francesco Chemello; Hui Li; Takahiko Nishiyama; Kenian Chen; Yu Zhang; Efraín Sánchez-Ortiz; Adeeb Alomar; Lin Xu; Ning Liu; Rhonda Bassel-Duby; Eric N. Olson (Molecular Therapy: Nucleic Acids, 2023)
Duchenne muscular dystrophy (DMD) is a fatal X-linked recessive disease of progressive muscle weakness and wasting caused by the absence of dystrophin protein. Current gene therapy approaches using antisense oligonucleotides require lifelong dosing and have limited efficacy in restoring dystrophin production. A gene editing approach could permanently correct the genome and restore dystrophin protein expression. Here, we describe single-swap editing, in which an adenine base editor edits a single base pair at a splice donor site or splice acceptor site to enable exon skipping or reframing. In human induced pluripotent stem cell-derived cardiomyocytes, we demonstrate that single-swap editing can enable beneficial exon skipping or reframing for the three most therapeutically relevant exons—DMD exons 45, 51, and 53—which could be beneficial for 30% of all DMD patients. Furthermore, an adeno-associated virus delivery method for base editing components can efficiently restore dystrophin production locally and systemically in skeletal and cardiac muscles of a DMD mouse model containing a deletion of Dmd exon 44. Our studies demonstrate single-swap editing as a potential gene editing therapy for common DMD mutations.